Paediatric acute care: Highlights from the Paediatric Acute Care–Advanced Paediatric Life Support Conference, Hobart, 2018. (27th March 2019) - Teo, Stephen Sze Shing; Oakley, Ed; Stanford, Jane; Cichero, Jane
Abstract: The Paediatric Acute Care Conference (PACC) is an annual conference organised by APLS Australia to advance paediatric acute care topics for clinicians in pre‐hospital medicine, EDs, acute paediatrics, intensive care and anaesthesia. The PACC 2018 was held in Hobart, Tasmania. We provide a summary of some of the presentations.